Cognitive-communication and psychosocial functioning 12 months after severe traumatic brain injury. (6th December 2018) - Tran, Sarah; Kenny, Belinda; Power, Emma; Tate, Robyn; McDonald, Skye; Heard, Rob; Togher, Leanne
ABSTRACT: Objective : Cognitive-communication deficits after severe Traumatic Brain Injury (TBI) may contribute to poor psychosocial functioning, however, the possible nature of this relationship remains unclear and warrants investigation. The current study explored the variance and correlations of a measure of cognitive-communication with a measure of psychosocial outcome in adults 12 months following TBI. Method : 36 adults with severe TBI evaluated at 12 months post-injury. Cognitive-communication skills were evaluated with the Functional Assessment of Verbal Reasoning and Executive Strategies (FAVRES), Sydney Psychosocial Reintegration Scale-2 (SPRS-2) Form A – Informant version assessed psychosocial functioning. Multiple regression analyses were used to investigate association between cognitive-communication and psychosocial outcomes. Results : Two measures of cognitive-communication assessment (Accuracy and Rationale of the FAVRES) contributed significantly to total psychosocial outcome (SPRS-2). Multiple regression analyses revealed these variables accounted for 29.1% of the variance. Cognitive-communication variables accounted for 24.0% and 28.6% of the Work/Leisure and Relationship domains of the SPRS-2. Conclusion : Cognitive-communication ability was significantly related to psychosocial functioning at 12 months post-TBI. Findings suggested continued speech pathology involvement in the post-acute stages of recovery may improve social, vocational and overall psychosocial functioning. The FAVRES is a promising cognitive-communication assessment for identification of treatable factors impacting psychosocial outcomes.